CHEMICAL CONSTITUENTS FROM THE STEM BARK OF Alangium kurzi, Craib - Sofyan M Nur; Soetijoso Soemitro; Husein Hernandi Bahti; Ponis Tarigan; Yue Mao Shen; Rymond J Rumampuk (Indonesian Journal of Chemistry, 2001)
Three new chemical constituents have been isolated from the stem bark of Alangium kurzii Craib. The structures were respectively determined to be 4-cyclohexene-1,2,3-triol 1, 3-β-stigmast-5-en-3-ol (β-sitosterol 2), and 3-O-β-D-glucopyranosyl-stigmast-5-ene (daucosterol 3). These compounds are preliminary isolated from this plant.